Quranic verses shaping Djem and false perception of Alevism in the society - Topuz, Birol (Penerbit Universiti Kebangsaan Malaysia, 2022)
It is seen that the Alevi-Sunni relations are mostly shaped by the stereotyped perceptions of the two groups about each other. In particular, the fact that Alevism is a closed society due to the pressure they have experienced throughout history has prevented them from being perceived correctly. As such, it is seen that there are many misconceptions about Alevis and their rituals that do not match the reality but are accepted as correct by the society. Due to the lack of communication that could not be developed through this "unknown" in the historical process, Alevi-Sunni relations have always been open to manipulations. As a matter of fact, it is seen that Alevis' relations with Islam, the Djem ceremonies that form the basis of Alevism, and the content of Djem ceremonies have always remained a mystery to Sunnis. Unfortunately, this misperception also reflected negatively on the communication between the two groups. As it is known, if stereotypes arise when there is incorrect information about the target group, the best way to correct them is to create common contact environments that will bring individuals to the right information. Here in this article, the unknown Djem ritual and especially the Qur'anic verses that they refer to during the Djem ceremonies are discussed.